Dynamically modeling the effective range of IL-2 dosage in the treatment of systemic lupus erythematosus - Xin Gao; Jing He; Xiaolin Sun; Fangting Li (iScience, 2022)
Summary: Systemic lupus erythematosus (SLE) is a complex systemic autoimmune disease characterized by an overactive immune response to self-antigen. The overactivation of CD4+ Foxp3− conventional T cells (Tcons) and the inactivation of CD4+ CD25+ Foxp3+ regulatory T cells (Tregs) play important roles in the progression of SLE. Clinical trials showed that low-dose interleukin-2 (IL-2) is effective in treating SLE. Here, we developed a mathematical model involving Tcons, Tregs, natural killer (NK) cells, and IL-2 to simulate the dynamic processes involved in the treatment of SLE. We found an effective range of IL-2 dosage defined by the Tcon/Treg ratio in SLE treatment, termed the IL-2 dosage therapeutic window (IDTW). Our results showed that high levels of self-antigen result in a narrow IDTW and high post-treatment Tcon/Treg ratio. Furthermore, we proposed a classification method based on the ratio of pre-treatment Treg to CD4+ T cells to predict the treatment outcome of SLE patients.